2022
DOI: 10.1002/jqs.3467
|View full text |Cite
|
Sign up to set email alerts
|

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20th century stratigraphic event signals

Abstract: The extensive array of mid‐20th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…a) Geological timescale for the Quaternary, as sanctioned by the International Union of Geological Sciences/International Commission on Stratigraphy, but with the Anthropocene added as a proposed new series/epoch. Ratified boundaries are identified by a golden spike symbol (indicating a Global boundary Stratotype Section and Point; GSSP); pending and proposed boundaries are marked by a grey spike symbol (from Head et al, 2022b). A new stage name (replacing Stage 8) would be based on the locality of the GSSP also defining the Anthropocene.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…a) Geological timescale for the Quaternary, as sanctioned by the International Union of Geological Sciences/International Commission on Stratigraphy, but with the Anthropocene added as a proposed new series/epoch. Ratified boundaries are identified by a golden spike symbol (indicating a Global boundary Stratotype Section and Point; GSSP); pending and proposed boundaries are marked by a grey spike symbol (from Head et al, 2022b). A new stage name (replacing Stage 8) would be based on the locality of the GSSP also defining the Anthropocene.…”
Section: Figurementioning
confidence: 99%
“…The inception of this Anthropocene is marked by a wide array of stratigraphic markers clustered around the mid-20th century (Waters et al, 2016(Waters et al, , 2023b; Fig. 1) known as the Great Acceleration Event Array (Head et al, 2022b;Waters et al, 2022).…”
mentioning
confidence: 99%
“…Waters et al, 2016). Researchers have strong opinions over where the base of the Anthropocene, as a new geological epoch, should be set and the various stratigraphic markers that could potentially be used to define it (Lewis and Maslin, 2015; Swindles et al, 2015; Waters et al, 2016; Head et al, 2022). Some recent studies have suggested that the Anthropocene should, instead, be defined as an ongoing geological event as it reflects the ongoing human impact on Planet Earth (see Gibbard et al, 2022; Edwards et al, 2022).…”
mentioning
confidence: 99%
“…The importance and urgency of this Research Topic follow extant research, from which three key points are apparent. First, there are likely to be COVID-like pandemics in the future, partly due to the Anthropocene epoch (8)(9)(10)(11). Second, although health services are certainly familiar with, if not accustomed to crisis management, many are ill-prepared for the system-wide effects-if not, seismic shift-associated with instances like COVID-19.…”
mentioning
confidence: 99%